2006
DOI: 10.1093/occmed/kql157
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in the health status of workers in small-scale enterprises

Abstract: Despite the cross-sectional design and only adjusting age as a potential confounder, higher proportions of HT, IGT, obesity and smoking in male workers were found in SSEs compared to larger organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…In general, occupational health activities are less sufficient in smallerscale enterprises 25,26) . A higher prevalence of hypertension, obesity, and smoking in male workers in smaller enterprises compared to those in larger organizations was also reported in Japan 27) . Therefore, the tendencies of occupational class inequalities in smaller-scale enterprises might be different from those in large-scale enterprises.…”
Section: Introductionmentioning
confidence: 64%
“…In general, occupational health activities are less sufficient in smallerscale enterprises 25,26) . A higher prevalence of hypertension, obesity, and smoking in male workers in smaller enterprises compared to those in larger organizations was also reported in Japan 27) . Therefore, the tendencies of occupational class inequalities in smaller-scale enterprises might be different from those in large-scale enterprises.…”
Section: Introductionmentioning
confidence: 64%
“…The national survey in 201423 ) showed that the corresponding prevalence of obesity were 20.9%, 27.2%, 30.9%, 34.4%, 31.2%, respectively, in men, and 10.4%, 15.9%, 17.0%, 23.7%, and 24.0% in women, respectively. Further, a previous study using health checkup data in 2000 from five occupational health organizations24 ) reported that, among men, prevalence of hypertension and obesity were slightly lower among workers in large-scale companies than those in small-scale enterprises. Thus, our finding of lower prevalence of hypertension and obesity than those in the national representative sample may be ascribed to the fact that our sample did not include workers in small and medium-sized enterprises.…”
Section: Discussionmentioning
confidence: 91%
“…First, the number of EAP contracted with SSE was small, and this suggests that few workers in SSE get services from EAP. Health status of workers in SSE is poorer compared to that of large enterprises 9) . An advantage of using EAP in SSE is that SSE, which lack their own on-site health staff [10][11][12] , can provide their employees with mental health services.…”
mentioning
confidence: 93%